1956
DOI: 10.1038/bjc.1956.36
|View full text |Cite
|
Sign up to set email alerts
|

Radiobiology of the C3H Mouse Mammary Carcinoma: Increased Radiosensitivity of the Tumour Induced by Inoculation of the Host with Radiation-Attenuated Isografts

Abstract: IN a previous communication (Cohen and Cohen, 1954b) it was noted that tumours arising from viable grafts of the C3H mammary carcinoma, which had been attenuated by sublethal doses of radiation immediately before implantation, were found, when subsequently irradiated in situ, to have a significantly increased radiosensitivity. The radiosensitization did not appear to be due to any permanent change in the tumour, or to any local reaction in the tumour bed, but could be explained only on the basis of a sublimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1970
1970
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 1 publication
(1 reference statement)
0
4
0
Order By: Relevance
“…Thus, following nephrectomy and radiotherapy to the renal bed and para-aortic nodes, specific active immunotherapy using a vaccine prepared from the patient's own irradiated tumour or, alternatively, specific adoptive immunotherapy with sensitised lymphocytes, may prove more effective in destroying residual malignant cells than irradiation alone. Cohen and Cohen (1956) and also Haddow and Alexander (1 964) reported an increased response to irradiation of experimental tumours following injections of irradiated tumour autograft. This might be explained by the destruction, through immunological mechanisms, of residual cells after eradication of the main tumour mass by conventional treatment.…”
Section: Immunotherapymentioning
confidence: 93%
“…Thus, following nephrectomy and radiotherapy to the renal bed and para-aortic nodes, specific active immunotherapy using a vaccine prepared from the patient's own irradiated tumour or, alternatively, specific adoptive immunotherapy with sensitised lymphocytes, may prove more effective in destroying residual malignant cells than irradiation alone. Cohen and Cohen (1956) and also Haddow and Alexander (1 964) reported an increased response to irradiation of experimental tumours following injections of irradiated tumour autograft. This might be explained by the destruction, through immunological mechanisms, of residual cells after eradication of the main tumour mass by conventional treatment.…”
Section: Immunotherapymentioning
confidence: 93%
“…Cohen (1960),Powerset al (1967) and Suit and Kastelan (1970) showed that the radiation dose required for local tumor control was increased when animals were imniunosuppressed. Conversely, tumors growing in preimmunized animals were more easily cured by local radiotherapy (Cohen and Cohen, 1956;Suit and Kastelan, 1970). The mechanism by which irradiation may augment the normal degree of tumor immunity possessed by animals bearing small tumors is not known.…”
Section: Discussionmentioning
confidence: 99%
“…THERE are well documented studies which show that host factors in the mouse are important determinants of tumour radiosensitivity (Cohen & Cohen, 1956;Haddow & Alexander, 1964;Powers et al, 1967;Maruyama, 1967;Suit & Kastelan, 1970). However, the biological mechanism which effects this improved response is not clearly understood (Song & Levitt, 1975;Johnson, 1978).…”
mentioning
confidence: 99%